Peningkatan Kompetensi Guru-Guru SMP 33 Solok Selatan Melalui Pelatihan Pengembangan Bahan Ajar Kontekstual Berdasarkan Pendekatan Saintifik - Hufri, Hufri; Dwiridal, Letmi; Amir, Harman (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The teacher realizes that learning requires students to be active in building their knowledge, and the teacher acts more as a facilitator and motivator. As a facilitator and motivator in learning activities, teachers are required to always improve their ability to prepare, implement and evaluate learning. The low ability of teachers to develop contextual teaching materials based on a scientific approach, even not infrequently the teachers feel they have not understood it to be one of the obstacles faced by teachers in improving the quality of learning. This training activity aims to provide knowledge about contextual learning, scientific approaches and the development of teaching materials, and conduct discussions and mentoring the development of contextual teaching materials based on a scientific approach to the teachers of SMPN 33 Solok Selatan. The activities carried out consisted of, (1) Providing knowledge about: (a). Contextual learning, (b) Scientific approach, (c) Development of teaching materials, (2) Guiding teachers for the manufacture of contextual teaching materials (LKPD / LKS) based on a scientific approach. The instrument used was a test of understanding of the material and questionnaire responses of trainees. The data analysis technique used is paired t test and percentage analysis. Based on the analysis of the results of the evaluation conducted it can be concluded, the training carried out has been able to improve the competence of teachers in developing contextual teaching materials based on a scientific approach, the training material provided can increase teacher competencies in developing teaching materials